Gastric outlet obstruction as manifestation of eosinophilic gastroenteritis - Vargas-Rubio, Rómulo (2020)
Eosinophilic gastroenteritis (EG) is a rare entity. We report a 55-year-old man had no previous atopy or allergic history, who presented abdominal pain and vomiting. Abdominal computed tomography and endoscopy ultrasonography demostrated gastric wall thickening with wall thickening of the superior duodenum, without defined mass or fluid collection. Gastrointestinal endoscopy confirmed thickening of prepyloric folds and superior duodenum with luminal stenosis. Parcial gastrectomy was performed due to absence of definitive diagnosis and suspicion of possible malignancy and diagnosis of gastric outlet obstruction. Histopathology was compatible with EG, treated with an 8-week long howed clinical improvement, weight gain and normalization of eosinophil count on peripheral blood.